Threshold - Flint, Eric; Spoor, Ryk E (Riverdale, N.Y. Baen London Diamond distributor, 2012)
When the strange fossil she's discovered had ended up giving her a trip to Mars, Helen Sutter thought she'd gone about as far as any paleontologist would ever go in her lifetime. But when you've also married A.J. Baker, overconfident super-sensor expert for the only private agency in space--the Ares Corporation--and your best friend is a former secret agent who's just signed on as the chief of security for the newly created and already emabttled Interplanetary Research Institute of the United Nations, there's always somewhere farther to go.
Originally published: 2010.
Includes an excerpt from ElfHome by Wen Spencer and War Maid's Choice by David Weber.
113935
Keywords: Women paleontologists -- Fiction; Interplanetary voyages -- Fiction; Science fiction; Fiction